THE SITUATION OF SOIL - TRANSMITTED HELMINTH AND FOOD-BORNE TREMATODE INFECTIONS IN TWO COMMUNES OF SIN HO DISTRICT, LAI CHAU PROVINCE, IN 2021. (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence and characteristics of soil - transmitted helminth and food-borne trematode infections among residents of Ta Ngao and Ta Phin communes, Sin Ho district, Lai Chau province in 2021.Subjects and methods: A cross-sectional study was conducted in November 2021 on 401 residents (199 from Ta Ngao, 202 from Ta Phin), aged 6–65 years. Stool samples were examined using the Kato–Katz technique.Results: A total of 242/401 individuals (60.3%) were infected with at least one species of soil - transmitted helminth or food-borne trematode. The prevalence in Ta Ngao (67.3%) was higher than in Ta Phin (53.5%) (OR=1.794; 95% CI: 1.196–2.691; p=0.003). Infection rates were similar in males (60.2%) and females (60.5%). The highest prevalence was in the 6–10 age group (76.1%) and the lowest in those over 60 years (50%). The prevalence of Ascaris lumbricoides, Trichuris trichiura, hookworm, and Paragonimus spp. was 35.9%, 10.7%, 23.7%, and 3.7%, respectively. Single-species infections accounted for 79.3%, co-infection with two species for 18.6%, and three species for 2.1%. All T. trichiura and hookworm infections were of light intensity. Among 144 cases of Ascaris lumbricoides, 6.9% were moderate intensity, 1.4% heavy intensity, and the rest were light intensity.Conclusion: The prevalence of soil - transmitted helminth and food-borne trematode infections in these two communes of Sin Ho district remains high. Regular deworming interventions and environmental hygiene education are needed to reduce prevalence and reinfection risk.
Keywords: : soil - transmitted helminth; food-borne trematode infections; paragonimus; Lai Chau; 2021